Multiaxial viscoplasticity modelling of power plant steel - Saad, Abdullah Aziz; Sun, Wei; Tobi, A.L. Mohd (Trans Tech Publications, 2016)
The thermo-mechanical fatigue (TMF) of power plant components is caused by the cyclic operation of power plant. A time-dependent plasticity model can be used to simulate the component response under cyclic thermo-mechanical loading. This paper is concerned with the modelling of thermo-mechanical behaviour of power plant steel under various loading conditions. Fully-reversed, strain-controlled tests were conducted on a parent material of P91 steel at high temperatures in order to determine material constants. A unified, Chaboche viscoplasticity model, was used to model the TMF behaviour of the steel. The multiaxial form of the Chaboche constitutive equations have been implemented in the finite element software and validated by comparing to experimental data. Simulation results have been compared with the results of anisothermal cyclic testing in order to validate the performance of the model in cyclic temperature conditions. The model’s performance under multiaxial stress conditions was investigated by testing and simulating the notched bar specimen under load-controlled conditions.